TOWARDS POSITIVE PEACE: MALAYSIA'S STRIDES IN WELL-FUNCTIONING GOVERNMENT AND SUSTAINABLE ECONOMIC DEVELOPMENT - Hafizah Abdul Rahim; Asmak Ab Rahman, (Journal of Human Development and Communication (JoHDeC), 2025)
Well-functioning Government (WFG) describes how countries are directed, controlled, and held accountable. Hence, a country implementing well-functioning government principles and practices will lead to success and peace. The WFG is one of the pillars of positive peace introduced by the Institute for Peace and Economics (IEP). Therefore, this study will explore how WFG, as the pillar of positive peace, influenced the Malaysian economy. The main objective of this research is to explore the concept of WFG as a pillar of peace and its characteristics practised in the Malaysian economy. This study employed generic qualitative analysis and reviewed past research on good governance practices in Malaysia. The content analysis has been undertaken for this study. The attributes discussed, including political stability, sound economic policies, efficient governance and regulation, investment in human capital, and fiscal responsibility, collectively contribute to Malaysia's enduring economic resilience and growth trajectory. It fosters peace by cultivating social harmony, equity, and sustainable development. In addition, this approach contributes to Malaysia's overall well-being and advancement since it facilitates a peaceful and prosperous society.